PERBANDINGAN NILAI PARAMETER INDEKS ERITROSIT PADA SAMPEL PASIEN GAGAL GINJAL KRONIS MULTITRANSFUSI DENGAN MASA SIMPAN 1, 2, DAN 3 HARI - Asnita, Julia; Syuhada, Syuhada; Damhuri, Fajriani; Nur, Muhammad (Jurnal Kesehatan Tambusai, 2024)
Chronic kidney failure patients can experience a decrease in hemoglobin levels during blood sampling for laboratory examination or hemodialysis which results in anemia in the patient. Chronic kidney failure patients who experience anemia can be treated with blood transfusions before and after hemodialysis. Giving blood transfusions to patients with chronic renal failure in stages to increase Hb as needed by the patient to prevent overload. Before a transfusion is carried out, there is a pre-transfusion examination, which is a series of examination procedures. One of the pre-transfusion checks is to carry out a crossmatch, to match the blood of the patient who wants to be transfused with the blood of the donor required before the patient is given blood. If there is no significant difference in the erythrocyte content, erythrocyte index MCV, MCH, MCHC, HB and hematocrit then it can be carried out one blood draw from a patient with kidney failure for 3 days for transfusion.